2017
DOI: 10.1155/2017/9265259
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Prospective Observational Cohort Study on the Prevalence and Primary Diagnostic Accuracy of Occult Vertebral Fractures in Aged Women with Acute Lower Back Pain Using Magnetic Resonance Imaging

Abstract: Background Elderly female patients complaints of acute low back pain (LBP) may involve vertebral fracture (VF), among which occult VF (OVF: early-stage VF without any morphological change) is often missed to be detected by primary X-ray examination. The current study aimed to investigate the prevalence of VF and OVF and the diagnostic accuracy of the initial X-ray in detecting OVF. Method Subjects were elderly women (>70 years old) complaining of acute LBP with an accurate onset date. Subjects underwent lumbar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Researchers have reported many features that distinguish the character of back pain of patients with compression fracture from that of patients without this type of injury. A seemingly simple assessment of the intensity of pain on NRS performed among women with vertebral fractures due to osteoporosis [ 25 , 26 ] demonstrated that patients with vertebral fractures experience much more severe pain compared with patients without fractures. This finding leads to the conclusion that osteoporotic fractures of the spine are in fact not asymptomatic [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have reported many features that distinguish the character of back pain of patients with compression fracture from that of patients without this type of injury. A seemingly simple assessment of the intensity of pain on NRS performed among women with vertebral fractures due to osteoporosis [ 25 , 26 ] demonstrated that patients with vertebral fractures experience much more severe pain compared with patients without fractures. This finding leads to the conclusion that osteoporotic fractures of the spine are in fact not asymptomatic [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were: (i) missing WS-locs; (ii) missing information on the referral reason; and (iii) metal hardware resulting in non-evaluable image quality. To investigate a representative patient population, the study was performed on all consecutive patients aged >65 years and not only >70 years as previously described (4).…”
Section: Methodsmentioning
confidence: 99%
“…In patients aged > 70 years with low back pain (LBP), radiographs are initially performed, even if the radiographic detection of the vertebral fractures is rather poor (4). To exclude some rather rare reasons for LBP such as infection, tumor, or metastases, magnetic resonance imaging (MRI) can be additionally obtained (5).…”
Section: Introductionmentioning
confidence: 99%
“…It is important not to dismiss patient symptoms based on normal radiographs since many patients with normal plain films may only have acute changes detectable on MRI. 26 Loss of vertebral height may not be evident at time of acute symptoms but can be evident on subsequent follow-up radiograph.…”
Section: Introductionmentioning
confidence: 99%